Pengujian Usability Aplikasi Mobile E-Surat Menggunakan User Experience Questionnaire (UEQ) - Binti Rahmadtul Ulfa; Awalludiyah Ambarwati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
CV ANT is a software house in the city of Surabaya. In 2019 the company produced a mobile e-mail application for one of its clients. At the end of 2021, the company took the initiative to update the application's User Interface and User Experience (UI/UX) design but there has been no testing for both the old and new versions of the design. This study conducted usability testing on the old and new versions of the e-mail mobile application design to find out whether the new design has a better user experience than the old version or not. The testing technique used is the User Experience Questionnaire (UEQ) and prototype testing using a task scenario in the new version design. As respondents, there are 23 users of the old version of the e-mail application. The UEQ technique produces scores for the new version design, namely the Attractiveness scale gets 2.4 (excellent), Dependability 2.3 (excellent), Efficiency 2.1 (excellent), Accuracy 2.2 (excellent), Stimulation 2.5 (excellent), and Novelty 1.5 (good). While the old version of the Attractiveness scale got 1.7 (good), Perspicuity 1.5 (above average), Efficiency 1.4 (above average), Dependability 1.6 (good), Stimulation 1.4 (good), and Novelty 0.5 (below average). So it can be concluded that the new version design has a better user experience than the old version design. However, there is still a need for improvement based on the results of prototype testing, which is 51 out of 100 with a Medium level.